Dampak Implementasi Model Early Warning Score Terhadap Mutu Pelayanan Rawat Inap - Sri Wulan Megawati; Septy Dian Sondari; Irisanna Tambunan (STIKes Karsa Husada Garut, 2021)
The quality of hospital services is determined by the mortality and morbidity rates, including services in inpatient rooms. One of the efforts to improve the quality related to patient safety in hospitals is the implementation of the Early Warning Score (EWS). Early warning score (EWS) is a parameter used to assess the deterioration of the patient's physiological condition by using seven parameters for assessing the patient's physiological response so that it can predict the outcome of the patient being treated. The purpose of this study was to analyze the impact of the application of EWS on the quality of inpatient services consisting of mortality (Net Death Rate), length of stay (Length of Stay), referral to HCU/ICU and activation of code blue. The research was carried out with the help of 4 enumerators. The population in this study were patients who were treated in an adult inpatient room with inclusion and exclusion criteria. The samples obtained were 278 patients with purposive consecutive sampling technique for 1 month. Data were analyzed by frequency distribution and correlation test using Chi-square. The results obtained indicate that there is no correlation between the EWS value and length of stay, while for mortality there is a correlation with the p-value <0.001. Referrals to the ICU/HCU and activation of code blue could not be analyzed due to the homogeneity of the data so that a larger number of samples and case variations were required. EWS can be used as a predictor of inpatient service quality by looking at patient outcomes.